Cognitive flexibility and attention to detail in adolescents and adults with severe forms of anorexia nervosa. (28th February 2022) - Berthoz, Sylvie; Maria, Anne‐Solène; Ringuenet, Damien; Bourdier, Léna; Nicolas, Isabelle; Blanchet, Corinne; Foulon, Christine; Lavoisy, Guillaume; Godart, Nathalie; Barry, Caroline
Abstract: Objective: To determine if adolescents and adults diagnosed with anorexia nervosa differ in their levels of cognitive flexibility and attention to detail independently of potential confounds. Method: Sixty‐two adolescents and 54 adults were assessed while receiving inpatient treatment and completed the following self‐reports: Eating Disorders Examination Questionnaire, Maudsley Obsessive Compulsive Inventory and Hospital Anxiety and Depression scale. Performance‐based evaluations included the Wisconsin Card Sorting Test Computerised Version, the Comprehensive Trail Making Test, the Brixton Spatial Anticipation Test, the Rey Complex Figure and the Group Embedded Figures Test. Results: Comparisons of the adolescents and adults with anorexia nervosa revealed no significant differences for any of the neuropsychological test scores even after adjusting for potential confounding factors. Neither cognitive flexibility nor attention to detail were associated with level of eating disorder symptomatology, depression, anxiety or obsessive‐compulsive symptomatology. Unlike age, illness duration was found weakly associated with perseverative errors Wisconsin Card Sorting Test and with the central coherence index of the Rey Complex Figure recall condition. Conclusions: Set‐shifting and central coherence performance were independent of age, clinical symptoms severity and emotional status. Additional studies on the relationship between the duration of anorexia nervosa and neuropsychological difficulties are needed. Highlights: Past studies among people suffering from anorexia nervosa that investigated if difficulties in cognitive flexibility and poor central coherence are independent of age have provided inconsistent results Adolescents and adults with severe anorexia nervosa obtained similar performances on a variety of task indexing set‐shifting and attention to details While age and neurocognitive performances were not associated, the longer the illness duration the lower the performances